Coastal circulation and water transport properties of the Red Sea Project lagoon. (May 2021) - Zhan, Peng; Krokos, George; Langodan, Sabique; Guo, Daquan; Dasari, Hari; Papadopoulos, Vassilis P.; Lermusiaux, Pierre F.J.; Knio, Omar M.; Hoteit, Ibrahim
Abstract: The Red Sea Project (RSP) is based on a coastal lagoon with over 90 pristine islands. The project intends to transform the Red Sea coast into a world-class tourist destination. To better understand the regional dynamics and water exchange scenarios in the lagoon, a high-resolution numerical model is implemented. The general and tidal circulation dynamics are then investigated with a particular focus on the response of the lagoon to strong wind jets. Significant variations in winter and summer circulation patterns are identified. The tidal amplitude inside the lagoon is greater than that outside, with strong tidal currents passing over its surrounding coral reef banks. The lagoon rapidly responds to the strong easterly wind jets that occur mainly in winter; it develops a reverse flow at greater depths, and the coastal water elevation is instantly affected. Lagrangian particle simulations are conducted to study the residence time of water in the lagoon. The results suggest that water renewal is slow in winter. Analysis of the Lagrangian coherent structures (LCS) reveals that water renewal is largely linked to the circulation patterns in the lagoon. In winter, the water becomes restricted in the central lagoon with only moderate exchange, whereas in summer, more circulation is observed with a higher degree of interaction between the central lagoon and external water. The results of LCS also highlight the tidal contribution to stirring and mixing while identifying the hotspots of the phenomenon. Our analysis demonstrates an effective approach for studying regional water mixing and connectivity, which could support coastal management in data-limited regions. Highlights: The RSP lagoon dynamics are governed by larger-scale circulation and tidal currents. Episodes of easterly winds modulate the lagoonal circulation, particularly in winter. The seasonally varying circulation controls the residence time in the RSP lagoon.